Biomechanical Perspectives on Concussion in Sport. Issue 3 (September 2016) - Rowson, Steven; Bland, Megan L.; Campolettano, Eamon T.; Press, Jaclyn N.; Rowson, Bethany; Smith, Jake A.; Sproule, David W.; Tyson, Abigail M.; Duma, Stefan M.
Abstract : Concussions can occur in any sport. Often, clinical and biomechanical research efforts are disconnected. This review paper analyzes current concussion issues in sports from a biomechanical perspective and is geared toward Sports Med professionals. Overarching themes of this review include the biomechanics of the brain during head impact, role of protective equipment, potential population-based differences in concussion tolerance, potential intervention strategies to reduce the incidence of injury, and common biomechanical misconceptions.